Effects of Group Size on Behavior, Reproduction, and mRNA Expression in Brains of Brandt’s Voles - Wei Lu; Shuli Huang; Jing Liu; Erdenetuya Batsuren; Guoliang Li; Xinru Wan; Jidong Zhao; Zuoxin Wang; Wenxuan Han; Zhibin Zhang (Brain Sciences, 2023)
For social animals, a moderate group size is greatly important to maintain their reproductive success. However, the underlying neurobiological mechanism of group size on behavior and reproduction has rarely been investigated. In this study, we examined the effects of group size (1, 2, 4 pairs of adult male and female voles raised per cage) on behavior and reproduction. Meanwhile, the mRNA expression of stress and reproduction response-related genes in male brains was detected. We found that Brandt’s voles (Lasiopodomys brandtii) in the large-sized group fight more severely than those in the small-sized group. Meanwhile, male voles were more anxious than females. The average number of embryos and litters per female in the medium-sized group was significantly higher than that of large-sized group. In male voles, stress- or reproduction-response mRNA expressions were more related to final group size or final density due to death caused by fighting. Our results indicated that a moderate group size was beneficial to the reproductive output of Brandt’s voles. Our study highlights the combined effects of stress- or reproduction-related gene expression or behavior in regulating the fitness of voles with different group sizes.